Dampak Penggunaan Teknologi Informasi dan Komunikasi Terhadap Minat Belajar Siswa di SMK Ganesa Satria Depok - Rr. Vemmi Kesuma Dewi; Denok Sunarsi; Irfan Rizka Akbar (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the impact of Information and Communication Technology Use of Students' interest in SMK Ganesa Satria Depok. The population in this study were the students in the audio-video engineering department where there were 2 (two) parallel classes with an average of 30 students of the class and performed randomly. From the preliminary sample of 20 respondents, there were only 8 questionnaires returned. From 8 questionnaires, there were 3 questionnaires that were not complete, so they had to be excluded from the analysis, so the total respondents in this research were 5 students. The hypothesis used in this study was calculated using the likert scale of 4 points. The results of this study show that Peggunaan Information Technology and Communications have a good impact on Student interest in SMK Ganesa Satria Depok.